PHENYLKETONURIA - YESTERDAY, TODAY.....TOMORROW - DR.K.RAMADEVI M.D (International Journal of Pharma and Bio Sciences, 2013)
Phenylketonuria is a genetic disorder wherein there is an inability to convert phenylalanine to tyrosine leading to toxic elevations of this aminoacid in the blood that ultimately causes mental retardation. This disease occurs at a frequency of 1 in 10,000 births. Early detection and appropriate therapy can prevent permanent brain damage. The historical aspects related to disease and the newer options for diagnosis and treatment are herewith presented.